Improving Non-Fiction Writing Skills Through a Project Based Learning Approach for Class VII G Students at SMPN 10 Mataram - Edi, Edi; Hanadi, Hanadi; Sinta, Sinta; Maysti, Maysti; Ainun, Ainun; Eka, Eka (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
Education is a forum for gaining knowledge and achieving goals. The curriculum becomes a guideline in organizing learning activities. SMP Negeri 10 Mataram has used the Merdeka Curriculum for classes VII and VIII, and has an educational goal so that students are able to understand the material well. The problem faced is the lack of non-fiction writing skills in class VII G students of SMP Negeri 10 Mataram caused by internal and external factors. Internal factors can be seen from the lack of student interest in the learning process. External factors arise when teachers choose inappropriate strategies and approaches. This research aims to improve non-fiction writing skills through the Project Based Learning (PJBL) approach for class VII students at SMP Negeri 10 Mataram. This research uses a quasi-experimental method with a pre-test and post-test with control group design. The research results showed that there was a significant difference between the non-fiction writing skills of students in the experimental class which used the PJBL approach and the control class which used traditional learning. The PJBL approach can improve the non-fiction writing skills of class VII students at SMP Negeri 10 Mataram.